PENGARUH KOMPETENSI GURU TERHADAP KEDISIPLINAN SISWA MADRASAH IBTIDAIYAH AL-BASYARIYAH BALONG - Aksib Choirozziyaadatas Sholihah; Saiful Anwar (Jurnal Keislaman, 2022)
This study aims to determine whether there is an influence of teacher competence either individually or simultaneously on students' discipline attitudes. This research method is quantitative and descriptive. In measuring the research variables, the researcher tested the instrument first, namely the validity and reliability tests, while measuring the two variables' influence using a simple linear correlation and regression formula. To prove these problems, the authors conducted research at MI Al-Basyariyah Balong with the object of study being teachers and students in grades IV, V and VI, taking samples of 63 students and 25 educators. Based on the results of the analysis of research data from the two variables, it can be concluded that there is a significant influence between teacher competence on student discipline at MI Al-Basyariyah Balong. This is evidenced by statistical calculation data with a correlation test that rcount is greater than rtable with a respondent's confidence level of 25 teachers and 63 students. The story of the influence of teacher competence on student discipline is 73.2%, and the rest is influenced by other factors not examined in this study.